MODELATION OF THE RADIATION CHARACTERISTICS OF THE GAS PHASE COMBUSTION PRODUCTS BASED ON HIGH THEMPERATURE ATLASES OF SPECTRAL LINE PARAMETERS - N. I. Moskalenko (Известия высших учебных заведений: Проблемы энергетики, 2019)
High temperature atlass of spectral lines parameters of the combustion production of energy fuels and their use for modeling the radiation characteristics of the optically active ingredients and radiation heat transfer in high structurally inhomogeneous multicomponent media are considering. The model of the absorption bands to determine the functions of spectral transmission and parameterization according to the results of numerical modelation performed by direct calculation of the fine structure of the emission (absorption) spectra, followed by their numerical integration. The results of the calculations are compared with the data of experimental studies.